2018
DOI: 10.1038/s41418-018-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor restricts astrocytic NLRP3 inflammasome activation via enhancing the interaction of β-arrestin2 and NLRP3

Abstract: Astrocytes are involved in the neuroinflammation of neurodegenerative diseases, such as Parkinson's disease (PD). Among the numerous inflammatory cytokines, interleukin-1β (IL-1β) produced by astrocytic Nod-like receptor protein (NLRP) inflammasome is crucial in the pathogenesis of PD. β-arrestin2-mediated dopamine D2 receptor (Drd2) signal transduction has been regarded as a potential anti-inflammatory target. Our previous study revealed that astrocytic Drd2 suppresses neuroinflammation in the central nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 57 publications
2
120
0
Order By: Relevance
“…83 Similarly, in an in vitro study DRD2 receptors inhibited NLRP3 inflammasome activation in a β-arrestin2-dependent manner, whereas in MPTP-induced PD, DRD2 reduced the caspase-1 and IL-1β levels in the midbrain. 84 Thus, it clearly demonstrates a correlation between the level of DA and microglial NLRP3 inflammasome activation in PD.…”
Section: Dopamine Receptor-mediated Nlrp3mentioning
confidence: 80%
“…83 Similarly, in an in vitro study DRD2 receptors inhibited NLRP3 inflammasome activation in a β-arrestin2-dependent manner, whereas in MPTP-induced PD, DRD2 reduced the caspase-1 and IL-1β levels in the midbrain. 84 Thus, it clearly demonstrates a correlation between the level of DA and microglial NLRP3 inflammasome activation in PD.…”
Section: Dopamine Receptor-mediated Nlrp3mentioning
confidence: 80%
“…In this study, we generated mice with the potential for DA neuron specific NLRP3 inflammasome hyperactivity and analyzed the animals throughout aging ( others who report suppression of NLRP3 inflammasome-driven inflammation dependent on the DRD1 dopamine receptor in bone marrow derived macrophages [67]. In a related report, astroglial DRD2 receptors are similarly implicated in suppression of NLRP3 inflammasome activity [68]. Critically, DA neurons express DRD2 autoreceptors that are involved in regulating the synthesis, release, and uptake of dopamine in presynaptic cells [69].…”
Section: Discussionmentioning
confidence: 99%
“…However, functional research on dopamine receptors has focused on neurons because dopamine is a well-known neurotransmitter. The function of astrocytic dopamine receptors was long overlooked until we recently reported that activation of the astrocytic dopamine D2 receptor (DRD2) can suppress neuroinflammation in PD 23,24 . Because GSH is mainly synthesized in astrocytes in the brain [25][26][27] and dopamine receptors on astrocytes are functional, we hypothesized that astrocytic dopamine receptors regulate GSH synthesis.…”
mentioning
confidence: 99%